Coexistence of Cavernous Hemangioma and Other Vascular Malformations of the Orbit: A Report of Three Cases. Issue 2 (April 2014) - Strianese, Diego; Napoli, Manuela; Russo, Carmela; D'Errico, Arianna; Scotti, Nadia; Puoti, Gianfranco; Bonavolontà, Giulio; Tranfa, Fausto; Briganti, Francesco
Coexistence of orbital cavernous hemangioma and other vascular malformations is unusual and few cases have been reported. We describe the clinical and radiological features of three cases of orbital cavernous hemangiomas associated with other vascular malformations, selected reviewing a series of 181 cases of cavernous hemangiomas. All patients were males (age ranging from 43 to 67 years) without vascular systemic disorders and/or a clinical syndrome. They experienced slow progressive exophthalmos. One of them developed acute pulsatile proptosis (case 2), while another experienced slow progressive diplopia (case 3). In one case vascular lesions were bilateral (case 3) and in two patients two different lesions coexisted in the same orbit (cases 1 and 2). All patients underwent surgical excision, which was partial in two cases. Two patients had cavernous hemangiomas in association with a venous malformation (a varix in case 1 and a lymphangioma in case 2), while in the other ones (case 3) cavernous hemangioma was associated with a low-flow arteriovenous malformation. No patient denied visual impairment postoperatively. Few cases of orbital cavernous hemangiomas coexisting with other vascular malformations have been reported in the literature. This entity seems to be an association of different variants of orbital vascular malformations, presenting with a wide spectrum of clinical forms and probably with the same pathogenesis.